Cancer surgery during COVID increased the patient mortality and the transmission risk to healthcare workers: results from a retrospective cohort study (NCT05240378) - Kishan Soni; J. F. Neville; Roli Purwar; Tarun Kumar; Ghanshyam Yadav; Nimisha Verma; Manoj Pandey (World Journal of Surgical Oncology, 2022)
Abstract Background India encountered two waves of COVID-19 pandemic with variability in its characteristics and severity. Concerns were raised over the safety of treatment, and higher morbidity was predicted for oncological surgery. The present study was conducted to evaluate and compare the rate of morbidity and mortality in patients undergoing curative surgery for cancer before and during the COVID-19 pandemic. Method The prospectively obtained clinical data of 1576 patients treated between April 2019 and May 2021 was reviewed; of these, 959 patients were operated before COVID-19 and 617 during the pandemic. The data on complications, deaths, confirmed or suspected COVID-19 cases, and COVID-19 infection among health workers (HCW) was extracted. Results A 35% fall in number of surgeries was seen during the COVID period; significant fall was seen in genital and esophageal cancer. There was no difference in postoperative complication; however, the postoperative mortality was significantly higher. A total of 71 patients had COVID-19, of which 62 were preoperative and 9 postoperative, while 30/38 healthcare workers contracted COVID-19, of which 7 had the infection twice and 3 were infected after two doses of vaccination; there was no mortality in healthcare workers. Conclusion The present study demonstrates higher mortality rates after surgery in cancer patients, with no significant change in morbidity rates. A substantial proportion of HCWs were also infected though there was no mortality among this group. The results suggest higher mortality in cancer patients despite following the guidelines and protocols.